L’héritage sémantique multiple dans l’approche orientée objets - Szramek-Karcz, Sonia (Neophilologica, 2015)
The paper presents the role of multiple semantic inheritance that may be used in the Object Oriented Approach (OOA). The aim of the OOA, proposed by Wiesław Banyś at the University of Silesia, is to organise the language description in the form of a lexical data base easily implemented and used in automatic translation. Semantic inheritance is one of the most important features of the AOO and takes place when an object or an object class inherits operations and/or attributes from its super-object class while multiple inheritance is when an object or an object class can inherit semantic characteristics from more than one super-class. Some Object-Oriented Programming languages let the implantation of multiple inheritance, which, if the procedure is not abused and treated as emergency solution, makes the AOO description responding to every modification of human language and reflects every new language item in that lexical date base.